Seroprevalence of SARS-CoV-2 Antibodies Among Blood Donors in Malaysia During the Pre-Vaccination Period. (March 2022) - Shukri, A.M.A.; Adnan, A.; Mui, W. Seok; Mohamad, M.; Kamal, F.; Khalid, Z.; Nawi, S.F.A. Mohd; Amin, N. Abu
Abstract : Purpose: We aimed to investigate the prevalence of antibodies against SARS-CoV-2 virus among blood donors in Klang Valley; a cohort that represent healthy individuals in a city which recorded a high number of COVID-19 infections in the country. Methods & Materials: A total of 806 blood donors at the National Blood Centre were recruited between February to March 2021 during the third wave of the pandemic in Malaysia, a period just prior to the national COVID-19 vaccination programme began. 5 ml of blood were collected from each donor and the serum was subjected to qualitative determination of antibodies against SARS-CoV-2 virus using two tests. The first test detected total antibodies against SARS CoV-2 nucleocapsid (N) [Elecsys® Anti-SARS-CoV-2 Electrochemiluminescence immunoassay (ECLIA), Roche Diagnostics] while the second test detected the total antibodies against SARS-CoV-2 receptor binding domain (RBD) [WANTAI SARS-CoV-2 Antibody (Enzyme linked immunoassay (ELISA), China]. The tests were performed according to the manufacturer guidelines. The sera which produced positive results from both screening tests were then subjected to quantitative determination of antibodies against SARS-CoV-2 RBD [Elecsys® Anti-SARS-CoV-2 S (ECLIA), Roche Diagnostics] Results: Out of 806 sera collected from the blood donors, qualitative screening of antibodies against SARS-CoV-2 virus showed 37 samples (4.59%) were positive for total antibodies against RBD, while 25 (3.10%) were positive against N proteins. 28 samples (3.47%) were tested positive by the quantitative determination of the antibodies. Conclusion: Our study revealed similar seroprevalence rate found in an identical study conducted in Los Angeles whereby 4.06% out of 865 collected sera were positive. While the blood donor population may not represent the Malaysian population in general, the finding of the seroprevalence in this group could indicate the rate of people infected with this virus is far more than reported and could aid public health decision making.